Application of Benson Relaxation Technique to Patients at Risk of Violent Behavior in the Work Area of UPTD Puskesmas Karangrejo in 2024 - Purwanto, Dedy; Agustriyani, Feri (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The purpose of this study was to apply the Benson Relaxation Technique to patients at risk of violent behavior in the Karangrejo Health Center UPTD Work Area in 2024. Method: The research method is a case study with a mental nursing approach by applying pre post test actions of benson relaxation therapy. The study used two mental patients with risk problems for violent behavior carried out in the work area of the UPTD Puskesmas Karangrejo in December 2024. Result: Assessment of the first patient is the name Mr. RS, male gender, 31 years old. The second patient Mr.A is 30 years old and male. Nursing diagnoses that arise risk of violent behavior. Planning used benson relaxation therapy on diagnoses of risk of violent behavior for 3 days of treatment. Conclusion: Nursing implementation carried out on clients is by applying the action of benson relaxation therapy, the resolved diagnosis is the risk of violent behavior.